A New Theoretical View of Rockburst and Its Engineering Application - Junfeng Pan; Shaohong Liu; Shuwen Wang; Yongxue Xia (Advances in Civil Engineering)
Traditionally, rockburst is considered as a dynamic phenomenon of sudden destruction of coal/rock mass. In this study, rockburst is treated as an event process rather than a phenomenon. This paper introduces typical rockburst process, its classification, mechanism of internal and external causes, and energy criterion. Analysis indicates that rockburst is a dynamic process that includes three sequential phases: burst start-up, burst energy transfer, and rockburst pressure behavior. Excessive static stress concentration in the strata nearby the target zone appears to be the internal cause of rockburst start-up, while the external cause is the disturbance of the static stress concentration and additional load transfer by the concentrated dynamic load occurred at further distance. Potential burst start-up area is the highest stress concentration zone within the region where stress is in the critical equilibrium state. With the identified internal and external factors that contribute to rockburst start-up, it is concluded that the rockburst preventive measures should focus on the monitoring and controlling of originating source of static and dynamic stress concentrations. Field practice proves that the reunderstanding of rockburst and the derived preventive measures are feasible and successful.